1998
DOI: 10.3109/14756369809021480
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Zinc Metallopeptidases by Flavonoids and Related Phenolic Compounds: Structure-Activity Relationships

Abstract: Flavonoids and other benzopyrone substances, having an appropriate hydroxylation profile, may inhibit the metalloenzymes leucine aminopeptidase (LAP), aminopeptidase M (AP-M), and carboxypeptidase A (CP-A). A structural feature that evidently favours the interaction between flavonoids and the three metalloenzymes is the 2,3-double bond conjugating the A and B rings and conferring a planar structure. This can be considered virtually indispensable for inhibition of the three metallopeptidases, though the hydroxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 19 publications
4
39
0
1
Order By: Relevance
“…The inhibition of ACE by anthocyanins 1 and 2, may be probably due to the rigid planar structure of the molecule and the presence of ortho-dihydroxylation on the aromatic ring (Parellada and Suarez, 1998), besides appropriate hydroxylation, also a planar structure is indispensable for the metallopeptidases inhibition. Anthocyanins are the major constituents in Hibiscus sabdariffa (Kong et al, 2003) and are used as food colouring agents (Esselen and Sammy, 1975), and diverse pharmacological investigations have demonstrated their antioxidant activity, protective effects against induced hepatic toxicity in rats, DNA damage and peroxidase activity in human's blood (Ali et al, 2005).…”
Section: Resultsmentioning
confidence: 98%
“…The inhibition of ACE by anthocyanins 1 and 2, may be probably due to the rigid planar structure of the molecule and the presence of ortho-dihydroxylation on the aromatic ring (Parellada and Suarez, 1998), besides appropriate hydroxylation, also a planar structure is indispensable for the metallopeptidases inhibition. Anthocyanins are the major constituents in Hibiscus sabdariffa (Kong et al, 2003) and are used as food colouring agents (Esselen and Sammy, 1975), and diverse pharmacological investigations have demonstrated their antioxidant activity, protective effects against induced hepatic toxicity in rats, DNA damage and peroxidase activity in human's blood (Ali et al, 2005).…”
Section: Resultsmentioning
confidence: 98%
“…Quantitative structure activity relationship (QSAR) analysis showed that the number of hydroxyl groups on the benzene ring played a crucial role for activity of phenolic compounds and that substitution of hydroxyl groups by methoxy groups decreased activity [48]. This might because that hydroxyl groups in a phenolic compound could come into being complexes with metal ions, which are an active center of ACE [49,50]. Therefore, the metal ions of ACE were reduced and ACE activity decreased.…”
Section: β-Sitosterol Glucoside (9)mentioning
confidence: 96%
“…M14 peptidases such as CPA and CPB, synthesized in the pancreas and secreted into the gastrointestinal tract, are the major zinc-dependent enzymes responsible for the release of the C-terminal amino acid residue from food protein [2]. Carboxypeptidase activity in the gastrointestinal tract may be modulated by dietary zinc [3, 4] or can be inhibited by some organic food components [57]. Also, changes in the genomic expression levels may control carboxypeptidase enzyme activity in digestion [8].…”
Section: Introductionmentioning
confidence: 99%